Synergistic effect of UV and L-ascorbic acid on the reduction of graphene oxide: Reduction kinetics and quantum chemical simulations - Go, Su-Hyeon; Kim, Hyungjun; Yu, Jaesang; You, Nam-Ho; Ku, Bon-Cheol; Kim, Young-Kwan (ELSEVIER SCIENCE BV, 2018)
A photochemical strategy for eco-friendly reduction of graphene oxide (GO) was developed by using L-ascorbic acid (L-AA) as a photosensitive reducing agent L-AA was excited and oxidized with deprotonation by UV irradiation (254 nm) and the proton coupled electron transfer induces chemical reduction of GO. This photochemical process is quite eco-friendly and scalable, and the reduction kinetics and degree of GO were highly enhanced. To understand the improved reduction power by UV light, the redox properties of L-AA in the ground and excited states were characterized by using quantum chemical simulations. Based on the results, we clearly demonstrated the mechanism how UV irradiation considerably enhances the reducing power of L-AA for the reduction of GO.
Keywords: NANOSHEETS; OXIDATION